Popular Phonetic Mapping in The Qur’an and Its Implications on Teaching Arabic for Non-Native Speakers - Thohir, Muhammad; Dzakiruddin, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2022)
The advantages of Arabic as the language of the Qur’an are its variety of sounds in each word with derivations in various forms and meanings. This study aimed to map popular phonetics with repetition rate in the Qur'an in order to build implicative concepts in Arabic learning for non-native speakers. The research used a qualitative approach with the type of literature research. As a preliminary research, data were obtained through documentary techniques from the Qur'an and Surah al-Wāqi'ah was taken as a data sourcebecause it represented the criteria as a popular surah. The analysis used a content analysis approach through the stages of condensation, presentation and conclusions. The results of the study was found that popular phonetics had vocal repetitions of 1,015 short vowels, 246 long vowels and 1,512 consonants. The results showed that the frequency of repetition of both vowels and consonants in the Qur’an had a phonetic sequence pattern from front to back, which was in line with Chomsky’s universal rules and the natural order hypothesis of Krashen. In addition, the results were complemented by the hypothetical presupposition of the implications in Arabic learning for non-native speakers, both linguistically, psychologically, and pedagogically.